ANATOMICAL CHANGES OF KEKABU WOOD (Bombax ceiba L.) DUE TO MECHANICAL DENSIFICATION - Krisdianto, Krisdianto; Balfas, Jamal (Indonesian Journal of Forestry Research, 2005)
Kekabu wood  (Bombax  ceiba L.), which is  locally known as kapok or randu  has long been planted  as crops troughout  the country, as fiber producer aimed for stuffing  pillow. This species is considered as a giant tree which could produce a large quantity of timber. Unfortunately, the timber is too soft, having low density and several physical defects during drying, limiting its uses in conventional wood processing. Any treatment which could significantly increase its structural density may be useful for diversifying the uses of this timber.   This study examined some anatomical changes that may exist during mechanical densification. Wood samples measuring 40 mm thick, 40 mm wide and 500 mm long were steamed at 126°C for 30 minutes prior to  pressing of 23.75 kg/cm.  Anatomical measures were undertaken using light microscope and scanning electron microscope  on both treated and untreated samples. Results showed that the treatment  significantly reduced void volume and ray distance of approximately a half the initial wood structure, followed by an increased in wood density of more than 50%.